Tailgut cyst mimicking second anal opening in an infant - Jay Lodhia; Mujaheed Suleman; Doreen Msemakweli; Joshua Tadayo; Patrick Amsi; David Msuya (Elsevier, 2023)
Tailgut cysts are rare tumors of embryonic remnant located in the retrorectal space. They are mostly asymptomatic hence diagnosis is incidental. They at times present with unspecific symptoms therefore are often misdiagnosed. Radiological imaging aids with the diagnosis and plan the surgical management. Surgeons should be well conversant to avoid complications. Herein we present an infant with a fistulating tailgut cyst who was successfully managed surgically.